Autoimmune Epilepsy - Novel Multidisciplinary Analysis, Discoveries and Insights - Levite, Mia; Goldberg, Hadassa (Frontiers in Immunology, 2022)
Epilepsy affects ~50 million people. In ~30% of epilepsy patients the etiology is unknown, and ~30% are unresponsive to Anti-Epilepsy-Drugs. Intractable epilepsy often leads to multiple seizures per day/week, lasting for years, and accompanied by cognitive/behavioral/psychiatric problems. This interdisciplinary scientific (not clinical) Perspective, discusses Autoimmune Epilepsy from immunological, neurological and basic-science angles, and includes summaries and novel discoveries, ideas, insights and recommendations. The pathological activity in vitro and in animal models of autoimmune antibodies to: AMPA-GluR3, NMDA-NR1, NMDA-NR2, GAD-65, GABA-R, GLY-R, VGKC, LGI1, CASPR2, and β2 GP1, found in epilepsy patient’s subpopulations, is summarized. AMPA-GluR3B antibodies seem the most exclusive and pathogenic: killing neural cells by three mechanisms: excitotoxicity, Reactive-Oxygen-Species, and complement, and inducing and/or promoting: brain damage, epilepsy, and behavioral impairments. Additional Autoimmune Epilepsy-related topics are discussed. 1.Few autoimmune antibodies tilt the balance between excitatory Glutamate and inhibitory GABA, thereby promoting neuropathology and epilepsy; 2.Most autoantigens have extracellular domains, or secreted; 3.Several autoantigens have ‘frenetic character’- undergoing dynamic changes that increase antigenicity; 4.Autoantigen’s mRNA is expressed in multiple tissues/organs outside the brain. If translated to proteins, systemic autoimmunity is expected; 5.Timing and cause-effect relationships of autoimmunity and epilepsy; 6.Autoimmune antibodies induce, and associate with, cognitive/behavioral/psychiatric impairments; 7.Epitope spreading; 8.Different T cell ‘faces’: Normal T cells are needed for healthy brain. Normal T cells are damaged by autoimmune antibodies to glutamate-receptors which they express, and maybe by other neurotransmitter-receptor antibodies. But autoimmune and/or cytotoxic T cells damage the brain; 9.HLA can confer susceptibility or protection from Autoimmune Epilepsy; 10.Therapeutic strategies.